The Role of Logistics Service Quality Dimensions in Shaping Customer Satisfaction and Repurchase Intention in Indonesia's Cross-Border E-Commerce - Kezia Angelina Hidayat; Fitri Novika Widjaja; Adhika Putra Wicaksono (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study examines the influence of Logistics Service Quality (LSQ) on customer satisfaction and repurchase intention in cross-border e-commerce in Indonesia. LSQ is measured through seven dimensions—delivery service quality, delivery information service, return logistics service, delivery stability, availability, price fairness, and cross-border shopping experience—and investigates customer satisfaction as a mediating factor in repurchase intention.Method: This study employed a causal quantitative method using the Structural Equation Modeling-Partial Least Square (SEM-PLS) technique via SmartPLS 4. Data were collected from 250 Zalora consumers using purposive sampling and a 1-5 Likert scale questionnaire, which was tested for validity and reliability.Result: The results show that return logistics service, delivery stability, availability, and cross-border shopping experience significantly affect customer satisfaction, while price fairness, cross-border shopping experience, and customer satisfaction significantly influence repurchase intention. Conversely, delivery service quality, delivery information service, and price fairness had no significant effect on customer satisfaction, indicating that these dimensions are not key determinants in cross-border e-commerce.Practical Implications for Economic Growth and Development: These findings have strategic implications for Indonesia’s e-commerce and logistics sectors, highlighting the need to enhance LSQ to build customer trust and loyalty, thereby supporting digital economy growth and national logistics competitiveness.Originality/Value: This study integrates seven LSQ dimensions to examine their effects on customer satisfaction and repurchase intention in cross-border fashion e-commerce in Indonesia. It extends prior research by addressing the limited exploration of the availability aspect, providing broader insights into key logistical factors influencing consumer behavior.